Asian Nursing Research September 2013 - Redaksi (Elsevier, 2013)
- Long-term Care Nurses' Communication Difficulties with People Living with Dementia in Taiwan - Cultural Adaptation and the Psychometric Properties of KOrean Version - Structural Equation Modeling on Life-World Integration in People with Severe Burns - Posture Management Program Based on Theory of Planned Behavior for Adolescents with Mild Idiopathic Scoliosis - Factors Influencing Post-Traumatic Stress in Korean FOrensic Science Investigators - Effects on Health Outcomes in Women With Breast Cancer